The development of a quantification method for measuring iridescence using sexually selected traits in the Gulf pipefish (Syngnathus scovelli) - Tosto, Nicole M.; Rose, Emily; Flanagan, Sarah P.; Mason, Heather D. (Frontiers in Marine Science, 2023)
Reliably quantifying the strength of visual sexual signals, such as iridescence, has been challenging across the field of evolutionary biology, but is critically important for studying biologically relevant trait variation. To address this issue, we present the Iridescence Detection and Isolation Algorithm (IDIA), which was designed to isolate the iridescent signal from photographs for quantification of ornamentation. The Gulf pipefish, Syngnathus scovelli, served as a model system for testing the limits of the algorithm, and was an ideal test case due to their female-specific iridescent bands on their abdomens with a large degree of among-individual variation. Specifically, we tested the repeatability of iridescence estimates in a variety of settings, including manual versus automated measurements, a gradient of lighting intensities, observational data from multiple populations, and in detecting exposure to synthetic estrogen. Using the IDIA, female iridescence was quantified in two ways with results indicating a manual measurement of each individual band may be more reliable than the automated measurement taken by drawing a polygon around all bands. However, the intensity of the lighting the photographs were taken in did not significantly affect repeatability of the measurement of iridescence no matter how it was taken. The IDIA was able to detect geographical variation in female ornamentation of S. scovelli, demonstrating that our automated approach can potentially replicate previously-described population-level variation. Differences in the iridescent signal were significant when comparing female pipefish from the Florida coast to females collected from the Texas coast, indicating the possibility that external factors, such as differing environmental conditions, could affect the strength of female visual signals. Lastly, the IDIA was applied in an ecotoxicology application to detect the development of iridescence in male pipefish exposed to synthetic estrogen. Exposed males began expressing banding patterns with iridescence levels within the range of females. The results from this study confirm the feasibility of using the IDIA for measuring iridescence in fish across a variety of applications.